2020
DOI: 10.1088/1402-4896/ab5fa5
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Heisenberg Algebras: periodicity and finite representation

Abstract: We consider the Generalized Heisenberg Algebra (GHA) and the deformed GHA with finite representations. We provide the necessary restriction on the characteristic function of the periodic GHA and that of the periodic deformed GHA and study particular examples. Then, we give a deformation of GHA raising operator of the Morse system and conclude that this system can be described by a periodic deformed GHA as it can be deduced from a nilpotent GHA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Furthermore, it has been shown that the GHA can be applied for physical systems involving known spectrum such as the square well potential [49], the Morse potential [50,51] and the Pöschl-Teller potential [11,52].…”
Section: Generalities On Ghamentioning
confidence: 99%
“…Furthermore, it has been shown that the GHA can be applied for physical systems involving known spectrum such as the square well potential [49], the Morse potential [50,51] and the Pöschl-Teller potential [11,52].…”
Section: Generalities On Ghamentioning
confidence: 99%